The potential of cardboard with plaster of paris in creating an artwork and commercial product / Zulkarnian Hassan and Siti Maryam Ali Yasin - Hassan, Zulkarnian; Ali Yasin, Siti Maryam (2013)
Art and design is a field that has plenty of beneficial knowledge which is inclusive of several aspects such as art, culture, religion, ethnicity and the country. It comes together with moral values, creativity, innovation and new designs without pushing aside one's custom and heritage background. To be at par with modern technology, many new young artists have come out with new inventions that help them to prove their talents in creating new, innovative materials. Therefore, the objective of this study is to find the potential of basic material which is the Plaster of Paris combined with recycled items "waste cardboard" in producing one product or an art piece. Results from a previous research entitled The Potential of Solid Waste Material to be used as Part of the Mixture in Reducing Weight in Making of Large Plaster Mould", have shown several potentials for future studies. The material has the potential to be used and introduced as new innovative material in the making of a certain product. Many artists in this field have been using basic materials such as wood, rock, cement, ceramic and others in producing their art work. They lack the initiative to use something new and fail to meet the demand of many local and foreign art collectors who have always been looking for something different. Often, the difficulty in methods of producing it, carving process and high cost of materials stand in the way of the artists' interest in experiments. Method of study involves strength and life span test of the material to ensure that the quality of the material produced is inclusive of safety aspects and its overall usage. Other than achieving its objective, this study also contributes to the preservation of nature through the use of recycled items which have the potential to create something new. Hence, this study gives a new innovative material to the artists and product manufacturer in designing something unique, valuable and aesthetic.